2015
DOI: 10.1111/epi.13267
|View full text |Cite
|
Sign up to set email alerts
|

Brivaracetam, a selective high‐affinity synaptic vesicle protein 2A (SV2A) ligand with preclinical evidence of high brain permeability and fast onset of action

Abstract: SUMMARYObjective: Rapid distribution to the brain is a prerequisite for antiepileptic drugs used for treatment of acute seizures. The preclinical studies described here investigated the high-affinity synaptic vesicle glycoprotein 2A (SV2A) antiepileptic drug brivaracetam (BRV) for its rate of brain penetration and its onset of action. BRV was compared with levetiracetam (LEV). Methods: In vitro permeation studies were performed using Caco-2 cells. Plasma and brain levels were measured over time after single or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
134
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 145 publications
(140 citation statements)
references
References 35 publications
4
134
0
2
Order By: Relevance
“…This may reflect a suboptimal SE treatment approach with insufficient doses of newer AEDs, or their prescriptions without or with underdosed benzodiazepines as first line treatment (34). However, in animal studies levetiracetam has shown a relatively slow penetration into the central nervous system, with latencies of more than 1 hour to achieve maximum concentrations in the cerebrospinal or in the brain extra-cerebral fluid (35)(36)(37). Animal studies with phenytoin, on the other side, shows maximum concentrations in cerebrospinal and brain extra-cerebral fluids within 9-13minutes and 39-34minutes, respectively (38).…”
Section: Discussionmentioning
confidence: 99%
“…This may reflect a suboptimal SE treatment approach with insufficient doses of newer AEDs, or their prescriptions without or with underdosed benzodiazepines as first line treatment (34). However, in animal studies levetiracetam has shown a relatively slow penetration into the central nervous system, with latencies of more than 1 hour to achieve maximum concentrations in the cerebrospinal or in the brain extra-cerebral fluid (35)(36)(37). Animal studies with phenytoin, on the other side, shows maximum concentrations in cerebrospinal and brain extra-cerebral fluids within 9-13minutes and 39-34minutes, respectively (38).…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11][12][13]. As per literature review, no LC-MS/MS method was available for determination of brivaracetam alone from rabit plasma, the validated method was successfully applied for the determination of Tmax, Cmax, AUC0→t and AUC0→α using rabbits as test animals.…”
Section: Discussionmentioning
confidence: 99%
“…Brivaracetam chemically is a 4-npropyl analog of levetiracetam and a racetam derivative with anticonvulsant properties [7,8]. Literature survey pharmacokinetics and metabolism of 14C-brivaracetam, metabolism studies of brivaracetam and gemfibrozil, clinical trials of adjunctive brivaracetam for refractory partial-onset seizures, identification of drug metabolites in human plasma or serum integrating metabolite prediction, by LC-HRMS methods are reported for the drug [9][10][11][12][13]. To best of our knowledge, no published LC-MS/MS-based methods for the pharmacokinetic study of brivaracetam in healthy rabbits.…”
Section: Introductionmentioning
confidence: 99%
“…LEV has only modest affinity for SV2A, but BRV is a selective, high-affinity SV2A ligand with promising antiepileptic properties and fast onset of action. BRV, which has rapid brain entry and fast brain SV2A occupancy [17], provides potent and complete seizure suppression in animal models of partial, generalized, and drug-resistant seizures [32].…”
Section: Discussionmentioning
confidence: 99%
“…Expression of SV2A is correlated with the clinical response to LEV and predicts LEV efficacy in patients with epilepsy secondary to tumor [15]. The novel LEV analogs, brivaracetam (BRV) and seletracetam, which are effective as an adjunctive treatment in epilepsy, also bind to SV2A [16,17].…”
Section: Introductionmentioning
confidence: 99%